2013
DOI: 10.1115/1.4025412
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotic Approach to Oblique Cross-Sectional Analysis of Beams

Abstract: Structural and aeroelastic analyses using beam theories by default choose a cross section that is perpendicular to the reference line. In several cases, such as swept wings with high AR, a beam theory that allows for the choice of a cross section that is oblique to the reference line may be more convenient. This work uses the variational asymptotic method (VAM) to develop such a beam theory. The problems addressed are the planar deformation of a strip and the full 3D deformation of a solid, prismatic, right-ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 27 publications
0
5
0
1
Order By: Relevance
“…Starting from this model, Hodges et al (2010) provide ways to recover stresses and strains, and they have shown the excellent accuracy of the model. More recently, Rajagopal et al (2012) have used the variational-asymptotic method for the analysis of initially curved isotropic strips, whereas Rajagopal and Hodges (2014) have used the same approach to perform oblique cross-section analysis. In both papers, the proposed approaches lead to accurate and promising results, although the generalization to non-prismatic beams does not seem to be available.…”
Section: Introductionmentioning
confidence: 99%
“…Starting from this model, Hodges et al (2010) provide ways to recover stresses and strains, and they have shown the excellent accuracy of the model. More recently, Rajagopal et al (2012) have used the variational-asymptotic method for the analysis of initially curved isotropic strips, whereas Rajagopal and Hodges (2014) have used the same approach to perform oblique cross-section analysis. In both papers, the proposed approaches lead to accurate and promising results, although the generalization to non-prismatic beams does not seem to be available.…”
Section: Introductionmentioning
confidence: 99%
“…The adopted geometrical description implies that cross-sections are non-orthogonal to the beam's neutral axis. Instead, orthogonality is preserved in the Cartesian coordinate system, noting similar methodology is adopted in related works (Balduzzi et al 2016;Gimena et al 2008;Rajagopal and Hodges 2014;Balduzzi et al 2017a, c, d;Mercuri et al 2020;Vilar et al 2021a). Consequently, the cross-sectional layer area A (k) and total cross-sectional area A are given by The domain of each layer Ω (k) is then defined by…”
Section: Problem Idealizationmentioning
confidence: 99%
“… 2016 ; Gimena et al. 2008 ; Rajagopal and Hodges 2014 ; Balduzzi et al. 2017a , c , d ; Mercuri et al.…”
Section: Problem Idealizationunclassified
“…Such a modeling choice is substantially different from standard modeling approach used for curved beams where the cross-section is assumed to be perpendicular to the centerline [2, Chapter IV], [33]. However, as discussed in [54], such an exotic choice may have advantages in several situations. Certainly, it allows to bypass the need of parametric definition of the beam centerline and the use of additional local coordinate systems, with the associated coordinate transformations and derivative chains.…”
Section: Problem Formulationmentioning
confidence: 99%